PEREMPUAN DALAM MASA REVOLUSI DALAM CERPEN S. RUKIAH: SEBUAH PEMBACAAN GINOKRITIK (Women during Revolution Time in S. Rukiah’s Short Story: A Gynocritical Reading) - Oktarina, Dwi; Tjahjandari, Lily Tjahjandari; Warsono, Sunu (Kandai, 2024)
The revolutionary period is described as an important chapter in modern Indonesian history. At this time, self-awareness as an independent nation was formed within the Indonesian people. As one of the women writers during the revolutionary era, Rukiah’s thoughts made enthusiasm within the framework of liberating women. This research seeks to reveal Rukiah's position as a woman writer by using the women as a writer or ginocritic approach in the short stories "Mak Esah" and "Istri Prajurit" in Tandus (first published in 1952 and reprinted in 2017). The results of the study show that Rukiah gives a picture of reality in her works. Apart from that, he also gave a portraits of life during the revolutionary period by using a straightforward language as well as symbolic language. From the results of the ginocritical reading, it was revealed that Rukiah really upholds the spirit of change for women. However, he has not shown any effort to support women's condition to be free from male oppression. The depiction of female characters physically and mentally has not shown Rukiah's alignment with the view of freeing women from oppression.Masa-masa revolusi digambarkan sebagai satu babak penting dalam sejarah Indonesia modern. Pada masa ini, kesadaran diri sebagai bangsa yang merdeka terbentuk dalam diri rakyat Indonesia. Sebagai salah satu perempuan pengarang di era revolusi, Rukiah hadir membawa pemikiran dan semangat dalam kerangka memerdekakan perempuan. Penelitian ini berusaha mengungkap gambaran posisi Rukiah sebagai seorang perempuan pengarang dengan menggunakan pendekatan women as a writer atau ginokritik dalam cerpen “Mak Esah” dan “Istri Prajurit” yang termaktub dalam Tandus (terbit pertama pada 1952 dan dicetak ulang pada 2017). Hasil kajian menunjukkan bahwa Rukiah memberi gambaran realitas dalam karya-karyanya. Selain itu, ia juga menuangkan potret kehidupan pada masa-masa revolusi dengan menggunakan gaya bahasa lugas sekaligus juga bahasa simbol. Dari hasil pembacaan ginokritik terungkap bahwa Rukiah memang menjunjung tinggi semangat perubahan bagi kaum perempuan. Akan tetapi, ia belum menunjukkan upaya mendukung kondisi perempuan untuk terlepas dari opresi laki-laki. Penggambaran karakter tokoh perempuan secara fisik maupun batiniah belum menunjukkan keberpihakan Rukiah pada pandangan untuk membebaskan kaum perempuan dari ketertindasan.